Once upon a time in the West - Leone, Sergio, 1929-1989.; Morsella, Fulvio; Donati, Sergio; Bertolucci, Bernardo; Argento, Dario; Morricone, Ennio; Cardinale, Claudia, 1939-; Fonda, Henry, 1905-1982.; Robards, Jason; Bronson, Charles, 1920-2003.; Ferzetti, Gabriele, 1925-2015; Strode, Woody; et al. (Hollywood Calif. : Paramount Pictures, 2010)
A mysterious loner, a falsely accused renegade, a young widow, a railroad magnate and his vicious hired gun cross paths in a tale of land grabbing, greed and murder in the old West.
Widescreen.
From a story by Dario Argento, Bernardo Bertolucci, Sergio Leone.
Originally released as a motion picture in 1968.
Special features: commentary featuring directors John Carpenter, John Milius & John Cox, film historians Sir Christopher Frayling & Dr. Sheldon Hall, plus cast & crew.
Director of photography, Tonino Delli Colli ; editor, Nino Baragli ; music, Ennio Morricone.
Claudia Cardinale, Henry Fonda, Jason Robards, Charles Bronson, Gabriele Ferzetti, Paolo Stoppa, Woody Strode, Jack Elam.
Keywords: Murder -- West (U.S.) -- Drama; Widows -- West (U.S.) -- Drama; Outlaws -- West (U.S.) -- Drama; Western films; Feature films